Pope John Paul II, Vatican II, and Capital Punishment - Bromberg, Howard (2007)
Part I of this Article describe s Pope John Paul II’s teaching on capital punishment as based on the Scriptures and expressed in Evangelium Vitae and the Catechism. Part II examines the authority with which this doctrine was issued. Part III suggests that this teaching represents the “traditional teaching of the Church,” although a “more perfect expression” of that teaching than has heretofore been recognized. Parts IV and V indicate why the papacy of John Paul II-—“this time, in which God in His hidden design has entrusted to me... very close to the year 2000”-—was ripe for this explicit articulation of the Church’s position. Part IV shows that the teaching corresponds with the Catholic understanding of the dignity of man and the nature of the state. Part V demonstrates that the teaching relies on the modern social fact of life imprisonment, made possible for the first time by technological and jurisprudential developments, as a non-lethal means to defend society